Analyse externe de l’intégration du tourisme alternatif dans un territoire marginalisé : le cas du Bajo Balsas au Mexique - Maxime Kieffer (Études Caribéennes)
The aim of this article is to analyse, from an external point of view, the pre-existent conditions at a local-regional level of a rural territory in Mexico, the Bajo Balsas, regarding the hypothetic integration of a community based tourism (CBT) activity. The analysis is about the external aspects of the host territory to be considered before the introduction of an activity of tourism, and about its intrinsic conditions. The results show that the territory does have specific aptitudes to implement a CBT activity such as the local and collective organizational capacity, the existence of a larger process of development and an interesting complementarity of natural and cultural resources. Nevertheless, the study also reveals numerous restrictions such as the negative image of the region and the lack of connexion and local infrastructure. Based on the results, some recommendations have been formulated at the attention of the actors implied in the development process and in the implementation of the CBT initiative.